Study of Lipid profile in a population of university students - Roberto Wagner Junior Freire de Freitas; Marcio Flavio Moura de Araujo; Adman Camara Soares Lima; Dayse Christina Rodrigues Pereira; Ana Maria Parente Garcia Alencar; Marta Maria Coelho Damasceno (Universidade de São Paulo, 2013)
OBJECTIVE: to evaluate the lipid profile in a population of university students. METHODS: cross-sectional study with 702 students, of both genders enrolled in various courses at a public university in Fortaleza-CE. The demographic data and data on lifestyle habits were collected through a self-administered questionnaire. The blood collection was performed in a clinical laboratory. RESULTS: showed a predominantly young population, with a mean age of 21.5 years with more females (62.7%). High levels of triglycerides, total cholesterol and cholesterol associated with low density lipoprotein (LDL-c) were found in 23.0%, 9.7% and 5.9% of students, respectively. The cholesterol associated with high density lipoprotein (HDL-c) was at reduced values in 12.0% of subjects and was significantly associated with smoking (p=0.0231) and physical inactivity (p=0.0357). CONCLUSION: changes in lipid profile are present in the young population and intervention studies should be encouraged in order to reduce the prevalence of cardiovascular disease in adulthood.